Effect of Various Anticoagulants on Ethinyl Estradiol and Levonorgestrel Analysis in Human Plasma in Vitro by Ultra Performance Liquid Chromatography Tandem Mass Spectrometry - Yahdiana Harahap (Journal of Global Pharma Technology, 2019)
Objective: This research objective is to evaluate the different types of anticoagulant to ethinyl estradiol and levonorgestrel analysis in plasma using ultra performance liquid chromatography tandem mass spectrometry. Method: Chromatography condition was obtained with Acquity® UPLC BEH C18 column (1.7 µm; 50 x 2.1 mm); mobile phase consisting 0.1% formic acid in water – acetonitrile under gradient elution ; flow rate of 0.3 mL/minute; column temperature of 40ºC; injection volume of 10.0 µL; 5-minute analysis time and prednisone as internal standard. Sample preparation used protein precipitation followed by liquid-liquid extraction. Results: There was a linear result ranging from 5-500 pg/mL concentration of ethinyl estradiol and 100-10,000 pg/ml concentration of levonorgestrel. There was no significant difference for stability and recovery of ethinyl estradiol and levonorgestrel in citrate, heparin, and EDTA plasma (p > 0.05; ANOVA). However, significant difference for peak area ratio (p < 0.05; Kruskal Wallis), between citrate, EDTA, and heparin plasma was observed. Conclusion: Citrate and heparin plasma analysis had better result than EDTA plasma analysis.Keywords: Ethinyl estradiol, Levonorgestrel, Prednisone, EDTA, Heparin, Citrate.